The Evolution of Time Preference with Aggregate Uncertainty - Robson, Arthur J.; Samuelson, Larry (American Economic Review, 2009)
We examine the evolutionary foundations of intertemporal preferences. When all the risk affecting survival and reproduction is idiosyncratic, evolution selects for agents who maximize the discounted sum of expected utility, discounting at the sum of the population growth rate and the mortality rate. Aggregate uncertainty concerning survival rates leads to discount rates that exceed the sum of population growth rate and death rate, and can push agents away from exponential discounting. (JEL D11, D81, D91)